CARBOHYDRATES - Andrews, E.C.; Carraway, Elise; Pointer, Jasmine (Buffalo, New York : KidHaven Publishing, 2025)
Starches are a kind of carbohydrate, a primary source of food for people. Wheat, rice, and potatoes are some of the most common forms of starches that many people love to eat. And french fries? They're starches too! This appealing book introduces readers to this important group of food, including where starches grow and the many ways they're prepared as foods. It also introduces them to the concept of nutrients and food science, which will inspire them to be more thoughtful about what they put on their plate and into their bodies"--
Includes index and glossary
Keywords: Grain -- Juvenile literature; Carbohydrates -- Juvenile literature; Juvenile literature; Juvenile works